1997
DOI: 10.1111/j.1440-1827.1997.tb04453.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bcl‐2 in human breast cancer: Correlation between hormone receptor status, p53 protein accumulation and DNA strand breaks associated with apoptosis

Abstract: The expression of Bcl-2, a suppressor of apoptotic cell death, was investigated in 52 invasive carcinomas of the breast using reverse transcription-polymerase chain reaction and immunohistochemical methods. After consideration of both sets of results, 42 tumors (80.8%) were confirmed to be positive (Bcl-2(+)) and 10 (19.2%) were judged negative (Bcl-2(-)) for Bcl-2 expression. Related factors (p53 protein accumulation, hormone receptor status and apoptotic cell index) were also examined using immunohistochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 16 publications
3
18
0
1
Order By: Relevance
“…Apoptotic index and Ki67 also correlated positively with high pathological grade. Apoptotic index has been previously shown to be associated with p53 overexpression, but inversely with bcl-2 and ER (Lipponen et al, 1994;Hori et al, 1997;Rochaix et al, 1999). A high proliferation rate in breast tumours is associated with a poorer prognosis (Meyer and Lee, 1980;Silvestrini et al, 1985) as is p53 expression (Silvestrini et al, 1993), whereas ER overexpression is associated with a more favourable prognosis (EBCTCG, 1998b).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic index and Ki67 also correlated positively with high pathological grade. Apoptotic index has been previously shown to be associated with p53 overexpression, but inversely with bcl-2 and ER (Lipponen et al, 1994;Hori et al, 1997;Rochaix et al, 1999). A high proliferation rate in breast tumours is associated with a poorer prognosis (Meyer and Lee, 1980;Silvestrini et al, 1985) as is p53 expression (Silvestrini et al, 1993), whereas ER overexpression is associated with a more favourable prognosis (EBCTCG, 1998b).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies on human cancer tissues had demonstrated a significant inverse relationship between Bcl-2 and p53 protein expression in non-small-cell lung cancers, 31,32 follicular lymphomas, 33 gastric carcinomas, 34 esophageal squamous cancers, 35 non-melanoma skin cancers, 36 and breast carcinomas. 37,38 In prostatic carcinomas 39 and colorectal adenomas and carcinomas, 40 the expressions of Bcl-2 and p53 proteins in the same tissue section were almost reciprocal. It appeared that alteration of both Bcl-2 and p53 proteins may be involved in a common genetic pathway that is shared by a number of different human cancers.…”
mentioning
confidence: 99%
“…6 The expression of this oncoprotein in breast cancers seems to be related to poor prognosis associated with a high histological grade, epidermal growth factor receptor (EGFR) positivity, and bcl-2 and oestrogen receptor (ER) negativity. [7][8][9][10][11][12][13][14][15][16] However, it should be noted that clinical pathological studies also report the coexpression of cytokeratin (CK) and vimentin in breast cancer as a more aggressive phenotype associated with poor prognosis. 17 18 This particular phenotype has been detected in a subset of normal breast epithelial cells that grows out of mammoplasty cultures, after most of the early passage cells have senesced.…”
mentioning
confidence: 99%